Karl Marx, the Theft of Wood, and Working-Class Composition: A Contribution to the Current Debate - Linebaugh, Peter (Social justice, 2013)
The article discusses an opposition to the view that analyzes crime in the 19th century terms of a "lumpenproletariat" against an "industrial proletariat" as it analyzes the capitalist organization and planning of labor markets. Topics discussed include Karl Marx's early writings on criminal law and the theft of wood as placed within the context of the real dynamics of capitalist accumulation and why Marx never returned to the systematic analysis of crime.